1977
DOI: 10.1128/aem.33.1.74-78.1977
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation in self-service automatic washers

Abstract: The potential for microbial transfer in self-service laundry washing machines was investigated by obtaining swab samples from the interior surfaces of commercial machines and wash water samples before and after disinfectant treatment. Three disinfectants (chlorine, a quaternary ammonium product, and a phenolic disinfectant) were used. Four self-service laundry facilities were sampled, with 10 replications of the procedure for each treatment at each location. Although washers were set on a warmwater setting, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A number of investigators have reported that bacteria, including coliforms, are frequently recovered from washed clothing, particularly when low water temperatures are used (Christian, Manchester, & Mellor, 1983; Davis & Ainsworth, 1989; Smith, Neil, Davidson, & Davidson, 1987). Studies of communal laundries demonstrate that the washing machines are contaminated after use and can colonize laundry between loads (Buford, Pickett, & Hartman, 1977; Legnani & Leoni, 1997). Hot water temperature (80 to 90°C) is more microbicidal, but machines are often used at temperatures of 25 to 60°C.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have reported that bacteria, including coliforms, are frequently recovered from washed clothing, particularly when low water temperatures are used (Christian, Manchester, & Mellor, 1983; Davis & Ainsworth, 1989; Smith, Neil, Davidson, & Davidson, 1987). Studies of communal laundries demonstrate that the washing machines are contaminated after use and can colonize laundry between loads (Buford, Pickett, & Hartman, 1977; Legnani & Leoni, 1997). Hot water temperature (80 to 90°C) is more microbicidal, but machines are often used at temperatures of 25 to 60°C.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated (McNeil & Chopper 1962;Wiksell et al 1973;Buford et al 1977) that appreciable numbers of organisms may be transferred from contaminated to uncontaminated linen when these are included in the same wash cycle and also between linens washed in separate cycles where transfer of contamination is probably effected by organisms adhering to the washer surfaces. Although the studies by Walter & Schillinger (1975) indicate little value in the use of hypochlorites, Wilkhoff et al (1971) and Buford et al (1977) have demonstrated that addition of quaternary ammonium, phenolic disinfectants or hypochlorites to machine-wash cycles will produce significantly greater reduction in the numbers of viable organisms present in fabrics and in the water used for washing them than can be achieved by use of hot water and detergent alone. It is therefore suggested that disinfectants may be of value in preventing transfer of infection in situations where heavy soiling of linens is known to have occurred although at the present time use of chemical disinfectants is not recommended in hospital laundries.…”
Section: (Iii) Clothing and Household Linenmentioning
confidence: 99%